2010
DOI: 10.1007/s11538-010-9570-z
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Nosocomial Transmission of Rotavirus in Pediatric Wards

Abstract: Nosocomial transmission of viral and bacterial infections is a major problem worldwide, affecting millions of patients (and causing hundreds of thousands of deaths) per year. Rotavirus infections affect most children worldwide at least once before age five. We present here deterministic and stochastic models for the transmission of rotavirus in a pediatric hospital ward and draw on published data to compare the efficacy of several possible control measures in reducing the number of infections during a 90-day o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 36 publications
0
5
0
1
Order By: Relevance
“…This is especially true for the description of the transmission dynamics of infectious diseases ranging from measles and pertussis to gonorrhea and in the prediction of the effects of public health interventions such as treatment and vaccination on these dynamics (Anderson and May 8 , Keeling and Rohani 9 ). In the last two decades, mathematical modeling has provided a very useful means to study the transmission dynamics of nosocomial pathogens in hospitals, including investigations of patient and health care worker (HCW) contact patterns, and HCW- and patient-mediated transmission, we refer to Austin and Anderson 10 , Bergstrom et al 11 , Bonten et al 12 , Chamchod and Ruan 13 , Cooper et al 14 , D’Agata et al 15 17 , Grundmann and Hellriegel 18 , Kribs-Zaleta et al 19 , Plipat et al 20 , Smith et al 21 , Webb et al. 22 , 23 , Lipsitch et al 24 , and the references cited therein.…”
Section: Introductionmentioning
confidence: 99%
“…This is especially true for the description of the transmission dynamics of infectious diseases ranging from measles and pertussis to gonorrhea and in the prediction of the effects of public health interventions such as treatment and vaccination on these dynamics (Anderson and May 8 , Keeling and Rohani 9 ). In the last two decades, mathematical modeling has provided a very useful means to study the transmission dynamics of nosocomial pathogens in hospitals, including investigations of patient and health care worker (HCW) contact patterns, and HCW- and patient-mediated transmission, we refer to Austin and Anderson 10 , Bergstrom et al 11 , Bonten et al 12 , Chamchod and Ruan 13 , Cooper et al 14 , D’Agata et al 15 17 , Grundmann and Hellriegel 18 , Kribs-Zaleta et al 19 , Plipat et al 20 , Smith et al 21 , Webb et al. 22 , 23 , Lipsitch et al 24 , and the references cited therein.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies developed both a stochastic and a deterministic version of a similar compartmental model to investigate whether projected intervention effects were partly a result of random fluctuation [18,35,40,[78][79][80]. Others use a deterministic model to interpret the findings of a stochastic model [81].…”
Section: Force Of Infectionmentioning
confidence: 99%
“…Metrics used to quantify goodness of fit include the least square criterion (minimisation of sums of squares between the observed data and the model predictions) [21,56,57,75], maximum likelihood estimation (identification of the parameter value(s) that makes the observed data most likely) [18,22,24,35,53,63,65,66] and since 2007, Bayesian methods; frequently using Markov Chain Monte Carlo (MCMC) approaches [19,32,40,41,50,58,64,76] or a combination of MCMC and maximum likelihood estimation [36,59]. A further seven studies reported fitting their models by comparing model predictions to observed epidemiological data but did not apply any formal quantitative approach [17,29,43,60,81,101,104].…”
Section: Model Fitting To Datamentioning
confidence: 99%
See 1 more Smart Citation
“…En este contexto, destacan dos limitaciones: organizativa, debida a la falta de una suficiente zona geográfica, y humana, por falta de personal. Como el riesgo de transmisión se debe no sólo a los pacientes sintomáticos sino también a los pacientes asintomáticos, cabe la posibilidad, en período epidémico, de que las medidas fracasen [33] .…”
Section: Virus Respiratorio Sincitialunclassified